Community Development as Micropolitics : Comparing Theories, Policies and Politics in America and Britain - Emejulu, Akwugo (Book collections on Project MUSE., 2015)
Community development is routinely invoked as a practical solution to a myriad of social problems, even though there is little consensus about its meaning and purpose. Through a comparative analysis of competing US and UK perspectives on community development since 1968, this book critically examines the contradictory ideas and practices that have shaped this field. Such an approach exposes problematic politics that have far-reaching consequences for those committed to working for social justice.